Psychologiedidaktik durch Kommunikationsanalyse - Scharlau, Ingrid; Schreiber, Christine; Patrzek, Justine (Psychologiedidaktik und Evaluation XIII)
Keywords: Unterrichtsfach Psychologie

Psychologie als Unterrichtsfach: Konzeption des Curriculums an der Universität Paderborn - Buhl, Heike M.; Scharlau, Ingrid; Patrzek, Justine; Hiller, Sara; Klingsieck, Katrin B. (Psychologiedidaktik und Evaluation XIII)
Keywords: Unterrichtsfach Psychologie

Profession und Disziplin. Ein Schreibgespräch über den Weg durch die Fächer, Schreibdidaktik als Feldforschung (und - nebenbei - die Rettung der Schriftkultur). - Karsten, Andrea; Weisberg, Jan (JoSch - Journal der Schreibwissenschaft)

Blätterwald zur Positionierung in akademischen Texten - Karsten, Andrea (Praxishandbuch Schreibdidaktik. Übungen zur Vermittlung wissenschaftlicher Schreibkompetenzen)

Schnelles inhaltliches Feedback zu Entwürfen - Scharlau, Ingrid; Heuer, Claudia (Wissenschaftliches Lesen und Schreiben vermitteln)

Psychological Feasibility of a Virtual Cycling Environment for Human-in-the-Loop Experiments - Stratmann, Lukas; Buse, Dominik S.; Heinovski, Julian; Klingler, Florian; Sommer, Christoph; Tünnermann, Jan; Scharlau, Ingrid; Dressler, Falko (INFORMATIK 2019: 50 Jahre Gesellschaft für Informatik – Informatik für Gesellschaft (Workshop-Beiträge))

Plunging into a world? A novel approach to undergraduates’ metaphors of reading - Scharlau, Ingrid; Körber, Miriam; Karsten, Andrea (Frontline Learning Research)
Although there is considerable research on and knowledge about students’ conceptual-izations of learning or academic practices and skills, the variability of these conceptu-alizations has been consistently neglected.In the present study, we address this varia-bility in the field of academic readingwith the help of a novel approach. Drawing on qualitative metaphor analysis, we report a detailed system of students’ conceptual met-aphors of reading. Ourspecific methodologicalapproach to identify the structure of these conceptual metaphorsallowsto analyze subjective agency on a lexical as well as grammatical level.The conceptual metaphors we identified by this method are markedly variable, although they create an overall impression of medium to low agency, that is a reader who is only weakly active or potent. Interrater reliability of the coding system was very good. We also report and analyze the frequency of the conceptual metaphors ina sample of 143 texts written by bachelor students.
Keywords: metaphor; conceptual metaphor; metaphor analysis; academic reading; transitivity

Welche Rolle spielen Fachkulturen heute? Bericht von einer Erkundungsstudie. - Scharlau, Ingrid; Huber, Ludwig (die hochschullehre)
With the present exploration, we aimed to answer the question whether distinct disciplinary cultures are present at today’s universities. To this purpose, we conducted 16 interviews with scholars from different disciplines. Qualitative analysis shows that disciplinary cultures in a narrow, epistemological sense (including forms of knowledge and work as well as organisation of teaching and learning) are perceived as distinct aspects of higher education and deemed important. Disciplinary cultures in a broader sense related to lifestyle and habitus, however, were hardly reported and not perceived as characteristic. Questions of social selectivity or inequality within universities were rarely touched in the interviews. Own cultures are typically described as rather heterogeneous, which is not the case for other cultures. Handling of possible cultures as well as differences by the interviewees turned out to be very cautious, at the same time restrained and respectful. Even where differences are observed or different values are revealed, there is little evidence of disputes. Consequences of these findings for research into disciplinary cultures and higher education are discussed.
Keywords: disciplinary culture; habitus; distinctions

The Role of Saliency in Learning First Words - Wildt, Eugenia; Rohlfing, Katharina; Scharlau, Ingrid (Frontiers in Psychology)

Assessing Self-Efficacy for Self-Regulation of Academic Writing: Development and validation of a scale - Golombek, Christiane; Klingsieck, Katrin B.; Scharlau, Ingrid (European Journal of Psychological Assessment)
Abstract. Academic writing is a complex and demanding activity that plays an important role in self-regulated learning settings within higher education. Self-efficacy and self-regulation are crucial factors for success and failure in academic writing. Because of the lack of adequate instruments, assessment of these factors is still limited. This paper introduces a scale for the assessment of self-efficacy for self-regulation of academic writing (SSAW). We deductively developed the SSAW scale and then conducted three studies in order to test and validate the scale. The first study ( N = 121) resulted in a brief scale with good psychometric properties. The second study ( N = 660) showed the scale’s factorial validity. The third study ( N = 188) provided evidence for the convergent validity of the SSAW scale. In sum, these studies yield a reliable, valid, and economic scale. The results are discussed with regard to the usefulness of the SSAW scale for research and practice in higher education.

Zur Positionierung der Forschung an Schreibzentren - Scharlau, Ingrid; Klingsieck, Katrin B. (Forschung für die Schreibdidaktik: Voraussetzung oder institutioneller Irrweg?)
Die Forderung nach evidenzbasierter Arbeit verbreitet sich zunehmend auch in der Hochschuldidaktik. In diesem Beitrag wird das Konzept der Evidenzbasierung kritisch analysiert und geprüft, ob bzw. unter welchen Bedingungen, es für die Bewertung schreibdidaktischer Arbeit taugt. Zudem werden alternative Überlegungen dazu, wie der Nutzen schreibdidaktischer Maßnahmen erkundet und geprüft werden kann, entwickelt.

How ideas come into being: Tracing intertextual moments in grades of objectification and publicness - Karsten, Andrea; Bertau, Marie-Cécile (Frontiers in Psychology)
How do ideas come into being? Our contribution takes its starting point in an observation we made in empirical data from a prior study. The data center around an instant of an academic writer’s thinking during the revision of a scientific paper. Through a detailed discourse-oriented micro-analysis, we zoom in on the writer’s thinking activity and uncover the genesis of a complex idea through a sequence of interrelated moments. These moments feature different degrees of “crystallization” of the idea; from gestures, a sketch, a short written note, oral explanations to a final spelled-out written argument. For this contribution, we re-analyze the material, asking how the idea gets formed during the thinking process and how it reaches a tangible form, which is understandable both for the thinker and for other persons. We root our analysis in a notion of language as social, embodied, and dialogical activity, drawing on concepts from Humboldt, Jakubinskij, and Vygotsky. We focus our analysis on three conceptual nodes. The first node is the ebbing and advancing of language in idea formation – observable as a trajectory through linguistically more condensed or more expanded utterance forms. The second node is the degree of objectification that the idea reaches when it is performed differently in a variety of addressivity constellations, i.e., whether and how it becomes understandable to the thinker and to others in the social sphere. Finally, the third node is the saturation of the idea through what we call intrapersonal intertextuality, i.e., its complex and dialogically related re-articulations in a sequence of formative moments. With these considerations, we articulate a clear consequence for theorizing thinking. We hold that thinking is social, embodied, and dialogically organized because it is entangled with language. Ideas come into being and become understandable and communicable to other persons only by and within their different, yet, intertextually related formations.
Keywords: idea formation; language activity; objectification; intrapersonal intertextuality; articulation; Jakubinskij; Vygotsky; Humboldt

Stuck on a plateau? A model-based approach to fundamental issues in visual temporal-order judgments - Tünnermann, Jan; Scharlau, Ingrid (Vision)

Reconsidering interiorization: Self moving across language spacetimes - Bertau, Marie-Cécile; Karsten, Andrea (New Ideas in Psychology)
Sociogenesis addresses a pervasive problem in psychology given by Cartesian dualism that assigns the mental an inner locus apart from material activity. Aligning ourselves to the ongoing critical discussions of interiorization in psychology, we explore the crucial notion of space by highlighting language as sociocultural and dialogical activity performed by other-oriented individuals. We discuss space in terms of the “language spacetime”, a symbolic, embodied formation of mutually positioned speaking and listening selves. This leads beyond the “inside-outside” container metaphor and allows for a reformulation of interiorization. Interiorization is conceptualized as a continuous series of different, though mutually related movements between self and other and self and self that lead to and are supported by specific formations in language activity: reversion, transposition, and decoupling. Along a short passage of a video-based interview, we trace the reversion of dialogical positions within the addressivity constellation of the two interlocutors, their interactive creation of a heterotopic spacetime, and the decoupling of one speaker's psychological activity from the concrete here-and-now and the present other by moving and acting into this new sphere. Interiorization appears as a movement at the border of past, present, and possible future(s).
Keywords: Interiorization; Dialogical self; Language activity; Voice; Vygotsky; Heterotopia; Video-confrontation

Fachsensibilität als Ressource für den Writing Fellow-Ansatz - Frahnert, Vanessa; Karsten, Andrea (Lehren und Lernen mit Writing Fellows. Beiträge zur Forschung, Evaluation und Adaption)
Vanessa Frahnert und Andrea Karsten stellen ihr Textograph*innen-Programm zur Unterstützung des Schreibens in der Lehre vor, das seit dem Sommersemester 2016 zum regelmäßigen Angebot des Kompetenzzentrums Schreiben der Universität Paderborn gehört. Das Programm baut auf den grundlegenden Prinzipien und Überlegungen des Writing Fellow-Konzepts auf, ist aber an die theoretische Ausrichtung des Schreibzentrums sowie die Gegebenheiten der Universität angepasst. Der Beitrag stellt das Programm und seine theoretischen Hintergründe vor und arbeitet die Unterschiede im Vergleich zum Writing Fellow-Ansatz heraus.

Am Schreiben teilhaben. Das Textograph*innen-Programm an der Universität Paderborn - Karsten, Andrea; Frahnert, Vanessa; Schäfer, Stefanie (Peer Learning an Hochschulen. Elemente einer diversitysensiblen, inklusiven Bildung)

Poking Left To Be Right? A Model-Based Analysis of Temporal Order Judged by Mice - Tünnermann, Jan; Scharlau, Ingrid (Advances in Cognitive Psychology)

Sich verständigen: Überlegungen zur Frage der Evidenzbasierung - Scharlau, Ingrid (Theorie und Praxis der Hochschulbildungsforschung: Für eine offene Zukunft der Hochschuldidaktik)
Evidenzbasierung ist in den vergangenen Jahren zu einem wichtigen Leitbild von Forschung in vielen praktisch relevanten Bereichen geworden und entwickelt sich zu einem solchen auch in der Hochschuldidaktik. Aufbauend auf einer kritischen Analyse der Leistungen von Metaanalysen und der Methodenkrise in der Psychologie sowie den besonderen Anforderungen an Erkenntnis in der Hochschuldidaktik fragt der vorliegende Beitrag, wie weit Evidenzbasierung die in sie gesetzten Erwartungen erfüllen kann und welche unbeabsichtigten Folgen sie hat.
Keywords: Evidenzbasierung; Methodenkrise; Fachkulturen

Hades - The Invisible Side of Mathematical Thinking - Paravicini, Walther; Schnieder, Jörn; Scharlau, Ingrid (Philosophy of mathematics education today)
The chapter presents a philosophical approach to teaching and learning mathematics in which five philosophical methods are translated into methods of reading and writing mathematical texts. The philosophical approaches are Hermeneutics, Analytical philosophy, Dialectics, Experience based (phenomenological) and Speculative philosophy. We use the acronym HADES for the combination of these approaches. For each of them we present reading and writing material which can be used for teaching peer tutors and by them in their interaction with students.

Wirksame Lese- und Schreibaufgaben für Studierende. Vortrag in der Didaktik-Lounge der FH Bielefeld. - Scharlau, Ingrid

Schreiben lehren: Eine fach- und diskurssensible Fortbildung für Lehrende (2) - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre. 86. Ergänzungslieferung)

Schreiben lehren: Eine fach- und diskurssensible Fortbildung für Lehrende (1) - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre. 85. Ergänzungslieferung)

Quantitative Explanation as a Tight Coupling of Data, Model, and Theory - Krüger, Alexander; Tünnermann, Jan; Rohlfing, Katharina; Scharlau, Ingrid (Archives of Data Science, Series A)
What does it mean to explain data patterns? Cognitive psychologists and other scientists face this question when observable phenomena have to be explained in theoretical terms. Frequentist null-hypothesis testing – one prominent approach in psychology – controls error rates. Machine learning – an alternative prominent outside of, but not yet inside psychology – focuses on precise predictions. However, both alternatives often provide little insight into the data. We propose a combination of formal modeling and Bayesian statistical inference to ground explanations in data analysis. We support this approach by reference to philosophy of science and discussions of the current methods crisis in several empirical sciences and illustrate it with an example from visual attention research.

Einheitlich, doch nicht ganz: Zur Fachdidaktik des Hochschul- und Schulfachs Psychologie. - Scharlau, Ingrid (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

Schreiben im Psychologiestudium - Scharlau, Ingrid; Klingsieck, Katrin

Schreiben im Psychologiestudium - Klingsieck, Katrin B.; Scharlau, Ingrid

Videokonfrontation als Methode für die angewandte Schreibforschung. Zwischen Investigation und Intervention - Karsten, Andrea (Qualitative Methoden in der Schreibforschung)

Zwei Varianten qualitativer Textanalyse zur Identifikation von Stimme(n) in Texten - Karsten, Andrea; Stock, Ingrid (Qualitative Methoden in der Schreibforschung)

Measuring and modeling salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
For almost three decades, the theory of visual attention (TVA) has been successful in mathematically describing and explaining a wide variety of phenomena in visual selection and recognition with high quantitative precision. Interestingly, the influence of feature contrast on attention has been included in TVA only recently, although it has been extensively studied outside the TVA framework. The present approach further develops this extension of TVA’s scope by measuring and modeling salience. An empirical measure of salience is achieved by linking different (orientation and luminance) contrasts to a TVA parameter. In the modeling part, the function relating feature contrasts to salience is described mathematically and tested against alternatives by Bayesian model comparison. This model comparison reveals that the power function is an appropriate model of salience growth in the dimensions of orientation and luminance contrast. Furthermore, if contrasts from the two dimensions are comb
Keywords: Salience; Visual attention; Bayesian inference; Theory of visual attention; Computational modeling; Inference; Object Recognition; Theories; Visual Perception; Visual Attention; Luminance; Perceptual Orientation; Statistical Probability; Stimulus Salience; Computational Modeling

Measuring Attention and Visual Processing Speed by Model-based Analysis of Temporal-order Judgments - Tünnermann, Jan; Krüger, Alexander; Scharlau, Ingrid (Journal of Visualized Experiments)
This protocol describes how to conduct temporal-order experiments to measure visual processing speed and the attentional resource distribution. The proposed method is based on a new and synergistic combination of three components: the temporal-order judgments (TOJ) paradigm, Bundesen's Theory of Visual Attention (TVA), and a hierarchical Bayesian estimation framework. The method provides readily interpretable parameters, which are supported by the theoretical and neurophysiological underpinnings of TVA. Using TOJs, TVA-based estimates can be obtained for a broad range of stimuli, whereas traditional paradigms used with TVA are mainly limited to letters and digits. Finally, the meaningful parameters of the proposed model allow for the establishment of a hierarchical Bayesian model. Such a statistical model allows assessing results in one coherent analysis both on the subject and the group level. To demonstrate the feasibility and versatility of this new approach, three experiments are reported with attention manipulations in synthetic pop-out displays, natural images, and a cued letter-report paradigm.

Gegen das weibliche Cooling-out in der Wissenschaft. Mentoring für Frauen in der Promotionsphase - Steinhausen, Julia; Scharlau, Ingrid (Praxishandbuch Mentoring in der Wissenschaft)

Diese Linie sollte man verlängern: Zum Verhältnis der Hochschuldidaktik zu den Fächern - Scharlau, Ingrid (Zwischen Wissenschaftsforschung, Wissenschaftspropädeutik und Hochschulpolitik. Hochschuldidaktik als lebendige Werkstatt. Festschrift für Ludwig Huber zum 80. Geburtstag)

Zugänge zur Erfassung der Schreibkompetenzen von Studierenden in lehrnahen Untersuchungen: Ein Methodenkompass - Scharlau, Ingrid; Golombek, Christiane; Klingsieck, Katrin B. (die hochschullehre)
Ziel dieses Beitrags ist die Vorstellung und Diskussion unterschiedlicher Methoden zur Erfassung von hochschulischen Lernprozessen. Den konzeptuellen Rahmen dafür bietet das Scholarship of Teaching and Learning (SoTL). Am Beispiel von Schreibkompetenzen werden Analysen von Textproben, Selbsteinschätzungen per Fragebogen und Interview, Protokolle lauten Denkens und standardisierte Testverfahren vorgestellt. Die Vor- und Nachteile jeder Methode werden anhand exemplarischer Fragestellungen diskutiert. Abschließend reflektiert der Beitrag die Frage, wie SoTL von Überlegungen aus mixed-methods-Ansätzen profitieren kann.

Schreiben eine Stimme geben. Über die Beziehung von lautem Sprechen und Schreiben im Schreibprozess - Lohmeier, Yvonne; Karsten, Andrea (JoSch – Journal der Schreibberatung)
Keywords: Schreibberatung; Schreibdidaktik; Schreibprozess; Sprache

Fast and conspicuous? Quantifying salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Advances in Cognitive Psychology)
Particular differences between an object and its surrounding cause salience, guide attention, and improve performance in various tasks. While much research has been dedicated to identifying which feature dimensions contribute to salience, much less regard has been paid to the quantitative strength of the salience caused by feature differences. Only a few studies systematically related salience effects to a common salience measure, and they are partly outdated in the light of new findings on the time course of salience effects. We propose Bundesen’s Theory of Visual Attention (TV A) as a theoretical basis for measuring salience and introduce an empirical and modeling approach to link this theory to data retrieved from temporal-order judgments. With this procedure, TV A becomes applicable to a broad range of salience-related stimulus material. Three experiments with orientation pop-out displays demonstrate the feasibility of the method. A 4th experiment substantiates its applicability t
Keywords: salience; visual attention; Bayesian inference; theory of visual attention; computational modeling; Visual Attention; Computational Modeling; Inference; Judgment; Statistical Probability

Peripheral visual cues: Their fate in processing and effects on attention and temporal-order perception. - Tünnermann, Jan; Scharlau, Ingrid (Frontiers in Psychology)
Peripheral visual cues lead to large shifts in psychometric distributions of temporal-order judgments. In one view, such shifts are attributed to attention speeding up processing of the cued stimulus, so-called prior entry. However, sometimes these shifts are so large that it is unlikely that they are caused by attention alone. Here we tested the prevalent alternative explanation that the cue is sometimes confused with the target on a perceptual level, bolstering the shift of the psychometric function. We applied a novel model of cued temporal-order judgments, derived from Bundesen’s Theory of Visual Attention.We found that cue–target confusions indeed contribute to shifting psychometric functions. However, cue-induced changes in the processing rates of the target stimuli play an important role, too. At smaller cueing intervals, the cue increased the processing speed of the target. At larger intervals, inhibition of return was predominant. Earlier studies of cued TOJs were insensitive
Keywords: cueing; temporal-order judgements; theory of visual attention (TVA); peripheral cue; processing speed; stimulus encoding; prior entry; Attention; Cues; Face Perception; Judgment

Writer’s overload: A multifaceted concept and its clarification. - Scharlau, Ingrid; Karsten, Andrea; Klingsieck, Katrin B. (die hochschullehre)
Many problems student writers are faced with can be understood as writer’s overload, the inability to tackle the high and complex concurrent demands of the writing process. In the present paper, we spell out multiple notions of writer’s overload from the perspectives of cognitive, educational, and sociocultural psychology in order to provide faculty from all disciplines with some background to understand their students’ writing problems. Starting from the Scholarship of Teaching and Learning approach, our aim is to provide teachers with ideas on how they can change crucial aspects of learning activities in their classes and of their teaching practice and study how this affects learning and writing in order to advance the teaching of writing.
Keywords: SoTL; student writing; writer's overload; writing block

(Un)diszipliniertes Schreiben? Schreiben lehren und lernen im Studium und in den Fächern an der Leuphana Universität - Heß, Christiane; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

"Das zu riskieren, ist schon eine große Tat": Ludwig Huber im Gespräch mit Ingrid Scharlau - Huber, Ludwig; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Attention, awareness, discipline, and effort: Die Liberal Arts und ein College in Deutschland - Beck, Karin; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Die Vergnügungen der anderen: Fachsensible Hochschuldidaktik als neuer Weg zwischen allgemeiner und fachspezifischer Hochschuldidaktik - Scharlau, Ingrid; Keding, Gesche (Pädagogische Hochschulentwicklung: von der Programmatik zur Implementierung)

Sich gar nicht erst im behaglichen Zuhause der eignen Disziplin einrichten: Eine fachfremde Hausarbeit im ersten Semester - Scharlau, Ingrid; Heß, Christiane (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

And now for something completely different - Lehren und Lernen angesichts digitaler Herausforderungen - Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Mathematik schreiben - Scharlau, Ingrid (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014)

Drei Einflüsse auf Schreibberatung und ein integriertes Modell der Selbststeuerung für Schreibberaterinnen und Schreibberater - Keding, Gesche; Scharlau, Ingrid (Schreibberatung und Schreibförderung. Impulse aus Theorie, Empirie und Praxis)

Reading mathematical texts with philosophical methods - Schnieder, Jörn; Scharlau, Ingrid (Special Issue: The Philosophy of Mathematics Education at ICME 13)
The paper presents a hermeneutic approach to teaching and learning mathematics in which the hermeneutic circle is translated into methods of reading mathematical texts with the help of the three decisive steps 1) making prior knowledge explicit, 2) interpreting texts, and 3) fusing horizons of prior understanding and text content.

Zwei Fenster mit verschiedener Sicht - Scharlau, Ingrid; Karsten, Andrea; Nettingsmeier, Pia; Golombek, Christiane; Schäfer, Stefanie (Akademisches Schreiben. Halbband 1: Vom Qualitätspakt Lehre geförderte Schreibzentren und Schreibwerkstätten)

Does attention speed up processing? Decreases and increases of processing rates in visual prior entry. - Tünnermann, Jan; Petersen, Anders; Scharlau, Ingrid (Journal of Vision)
Selective visual attention improves performance in many tasks. Among others, it leads to 'prior entry'—earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen’s Theory of Visual Attention, which we use to overcome the limitations of earlier prior-entry assessment with temporal order judgments (TOJs) that only allow relative statements regarding the processing speed of attended and unattended stimuli. Prevalent models of prior entry in TOJs either indirectly predict a pure acceleration or cannot model the difference between acceleration and deceleration. In a paradigm that combines a letter-identification task with TOJs, we show that indeed acceleration of the attended and deceler
Keywords: unattended stimuli; attention speed; cognitive processing; Attention; Humans; Judgment; Mental Recall; Visual Perception; Stimulus Parameters; Visual Perception; Visual Attention; Cognitive Processes; Velocity

Fachsensible Hochschuldidaktik - Scharlau, Ingrid (Teaching is touching the future: Academic teaching within and across disciplines)

Nur Zahlen und Zeichen? Zum Nutzen des Schreibens in der Hochschuldidaktik der Mathematik - Scharlau, Ingrid; Heß, Christiane; Schnieder, Jörn (Neues Handbuch Hochschullehre. 70. Ergänzungslieferung)